Development of Transboundary Trade and Economic Relations in Central Asia: Challenges and Solutions - Mehri Vokhidova; Yuanis Yuanis (Indonesian Journal of Law and Economics Review, 2020)
This article will cover a wide range of key issues in the economies of the Central Asian countries, the extent of their development and opportunities for trade and economic relations. The aim of the study is to analyze trends and opportunities for improving trade and economic relations between the countries of Central Asia. The objectives of the study are: - to analyze the volume and tendency of GDP of Central Asian countries for 2000-2018; - analysis of the GDP per capita in the countries of Central Asia; - Comparative analysis of export and import volume, structure of export and import of Central Asian countries; - to study the relations of Central Asian countries with international organizations and to find mutual interests; - Identification of political, economic and social problems that impede the development of trade and economic relations in Central Asian countries. The results are as follows: - the main focus of improving trade and economic relations between the countries of Central Asia on the border of two or more countries is the Free Economic Zone; - Diversification of the economies of Uzbekistan and Kazakhstan in relation to other countries in the region can be a key factor in the development of trade and economic relations; - Expanding the role of regional organizations and integration in improving trade and economic relations between Central Asian countries. - The practical result of the establishment of transboundary free economic zones in Central Asia.